Agricultura familiar em Rio Claro - SP: em busca de alternativas para permanência no campo - Rosa, Fernando Amorim [UNESP] (Universidade Estadual Paulista (Unesp), 2012)
As we focusing in the Brazilian rural area we see that it presents the spatial diversity and the different organization forms of the space arising from its diversity, tied to the different economic, social, politic and cultural contexts .These contextual diversities bring results that is not limited to the agrarian sector, but get beyond the border of the rural world, taking different ways of organization and structuring in the urban areas. The building and management of the rural spaces are constituted as an attribute of the agricultural production that in the course of the centuries made disappear and reduce significant proportions from the natural areas. In many places, the intensification of the production process gives satisfaction to the globalized markets and that return allows the reproduction of the productive conditions. In other areas the access difficulties to the market and the proximity to the developed urban centers cause the abandonment of the agricultural activity and the maintenance of property without production or with specific services (tourism, for example). That process triggers a multiplicity of factors that are defining the pace of the rural areas in Brazil. This work sought to understand all the deals of the ‘’rural’’ county of Rio Claro-SP and what’s the role and the situation that we find the familiar agriculture in the advanced urban areas, which is the case of this study. Where the agriculture doesn’t represent the flagship of the economy. It was the intention, identify what activities and practices socio-spatial are developed in the county rural area. Trying to understand the public politics acts in the promotion and encouragement to the already developed activities or even other activities that can represent the possibility of a social and territorial reproduction of the families on the country

Ao voltarmos nossas atenções para o campo brasileiro notamos que este apresenta como uma de suas características mais marcantes a diversidade espacial e as diferentes formas de organização do espaço decorrentes desta diversidade, atrelada a distintos contextos econômicos, sociais, políticos e culturais. Tal diversidade e multiplicidade de contextos têm resultados que não se limitam ao espaço agrário, mas que extrapolam as fronteiras do mundo rural, levando a diferentes formas de organização e estruturação também de áreas urbanas. A formação e gestão dos espaços rurais têm se constituído como um atributo da produção agrícola que no decorrer de séculos fez desaparecer ou diminuir parcelas significativas de áreas naturais. Em muitos lugares a intensificação da produção se dá face à satisfação de mercados globalizados e cuja rentabilidade permite a reprodução de suas condições produtivas. Em outras áreas as dificuldades de acesso ao mercado e a proximidade de centros urbanos bastante desenvolvidos fazem com que ocorra o abandono da atividade agrícola e a manutenção da propriedade sem produção ou com a realização de serviços específicos (turismo, por exemplo). Tal processo desencadeia uma complexidade de fatores que tem demarcado o ritmo das áreas rurais no Brasil. Assim, neste trabalho buscou-se compreender toda a problemática do “rural” no município de Rio Claro - SP e qual o papel desempenhado e a situação em que se encontra a agricultura familiar em áreas de urbanização avançada, como é o caso da área deste estudo, onde a agricultura não se apresenta como o carro chefe da economia. Buscou-se, desta forma, identificar quais atividades e práticas socioespaciais são desenvolvidas na área rural do município. Procurando-se, também, compreender a atuação das políticas públicas na promoção e incentivo às atividades já desenvolvidas ou mesmo a outras atividades
Keywords: Agricultura; Agricultura familiar; Politicas publicas; Agricultura em tempo parcial; Rio Claro (SP)